Clinical significance of circulating immune cells in left- and right-sided colon cancer - Jiabo Di; Meng Zhuang; Hong Yang; Beihai Jiang; Zaozao Wang; Xiangqian Su (PeerJ, 2017)
Background Left-sided and right-sided colon cancers (LCCs and RCCs, respectively) differ in their epidemiology, pathogenesis, genetic and epigenetic alterations, molecular pathways and prognosis. Notably, immune response gene expression profiles have been shown to differ between patients with LCC and patients with RCC. The immune system plays an important role in tumor immunosurveillance, and there is increasing evidence that peripheral blood immune cells have a profound influence on tumor prognosis. This study aimed to determine the clinical significance of circulating immune cells with respect to colon tumor locations. Methods Different types of circulating immune cells were separated and analysed based on their surface markers by flow cytometry. We compared the numbers of dendritic cells (DCs) and T cell subsets in the peripheral blood of 94 patients with RCC or LCC and analysed the proportions of these immune cells in relation to tumor stage, tumor differentiation and lymphatic metastasis. Results We show that at later tumor stages, patients with LCC had higher levels of circulating myeloid DCs (P = 0.049) and plasmacytoid DCs (P = 0.018) than patients with RCC. In poorly differentiated tumors, LCC patients had significantly higher amount of plasmacytoid DCs (P = 0.036), CD4+ memory T (Tm) cells (P = 0.012), CD4+ T cells (P = 0.028), Tm cells (P = 0.014), and regulatory T cells (P = 0.001) than RCC patients. The levels of circulating CD4+ T cells, Tm cells and CD4+ Tm cells were significantly elevated at later stages in patients with LCC or RCC, while these cells decreased in poorly differentiated tumors in patients with RCC. Moreover, CD4+ Tm cell and CD4+ T cell levels are significantly associated with lymph node metastasis in patients with LCC and RCC. Discussion Circulating immune cells were associated with tumor location, tumor stage and tumor differentiation, and can be used to predict lymphatic metastasis in patients with colon cancer. This variation in systemic immunity could contribute to the differential prognosis of patients with colon cancer.